The Influence of Contextual Teaching and Learning (CTL) and Self-Confidence on Junior High School Students' Mathematics Learning Achievement - Siahaan, Natalia; Rohman, Ujang; Suharti, Suharti (Gema Wiralodra, 2025)
This study aims to examine the influence of Contextual Teaching and Learning (CTL) and self-confidence on the mathematics learning achievement of junior high school students. Mathematics is often considered a difficult subject, and this perception is influenced by both instructional methods and students’ psychological attributes, such as self-confidence. A quantitative approach with a 2×2 factorial design was employed. The sample consisted of 80 eighth-grade students selected through purposive sampling from several junior high schools. Students were categorized based on teaching method (CTL vs. conventional) and levels of self-confidence (high vs. low). Data were analyzed using a two-way ANOVA. The results showed that both CTL and self-confidence had a significant effect on mathematics achievement (F = 8.92, p < 0.05 and F = 11.21, p < 0.05, respectively). Furthermore, there was a significant interaction between teaching method and self-confidence (F = 6.98, p < 0.05). These findings suggest that the implementation of CTL is more effective for students with high self-confidence and that students’ psychological readiness plays an important role in academic success. This research implies that mathematics learning should not only focus on instructional strategy but also on developing students’ self-confidence. Integrating CTL with efforts to enhance student confidence can significantly improve mathematics learning outcomes in junior high schools.